Internal Clocks, mGluR7 and Microtubules: A Primer for the Molecular Encoding of Target Durations in Cerebellar Purkinje Cells and Striatal Medium Spiny Neurons - Yousefzadeh, S. Aryana; Hesslow, Germund; Shumyatsky, Gleb P.; Meck, Warren H. (Frontiers in Molecular Neuroscience, 2020)
The majority of studies in the field of timing and time perception have generally focused on discrete neuronal circuits, behavioral paradigms, and timescales. Here, in an attempt to find common elements from a broader perspective, we review the literature and highlight the need for cell and molecular studies that can delineate the neural mechanisms underlying temporal processing. Moreover, given the recent attention to the microtubule proteins in neurons and their contributions to learning, memory, and consolidation/reconsolidation, we propose that these proteins might play key roles in coding temporal information in cerebellar Purkinje cells and striatal medium spiny neurons. Microtubule proteins’ widespread presence at appropriate neuronal sites, as well as its adaptability, dynamic structure, and longevity of storage, makes them a suitable candidate for creating plasticity at both intra- and inter-cellular levels. Thus, microtubules might be capable of maintaining a temporal code or engram and thereby regulate the firing patterns of Purkinje cells and medium spiny neurons. This proposed mechanism would control the storage of temporal information triggered by postsynaptic activation of mGluR7 which leads to alterations in microtubule dynamics through a ‘read-write’ memory process involving alterations in microtubule dynamics and their hexagonal lattice structures.